(untitled) (Tidsskrift for Praktisk Teologi, 2023)
This article examines a contemplative exercise in a confirmation class of the Evangelical Lutheran Church in Denmark. Each confirmand is asked to lie down in a pew isolated from the rest of the class and to meditate on prayer and scripture in the dim light of the sanctuary while contemplative music is played. This article raises questions about the learning process and the role of the minister. It focuses on what happens when learning modes shift from addressing what religion, as a system of knowledge, objectively is, to practised religion (how it is done) and to its more subjective form, religion as faith or experience. A problem is rooted in a conflict among these three aspects of religion and the associated modes of learning, which reveals a tension between external objectivity and the internal nature of subjectivity.